PENGARUH DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET KABUPATEN BARITO TIMUR. - Nana Wariati; Dahniar; Tinik Sugiati (Universitas Lambung Mangkurat, 2015)
This study was conducted to determine and analyze the influence of labor discipline and work experience on the performance of employees at the Department of Finance and Asset Management Revenue East Barito Regency either simultaneously or partially. The independent variables were examined consisted of work discipline variables (X1), work experience (X2), while the dependent variable is the performance of employees (Y) This type of research uses explanatory research. The study population includes employees of the Department of Finance and Asset Management Revenue East Barito District totaling 67 people who serve as the respondent, using census / saturation sampling, data analysis using multiple linear regression. Results showed simultaneously through the F test in the can that work discipline variable (X1) and work experience (X2) bepengaruh significantly on employee performance (Y). Partially through t test, in that the independent variables which can include work discipline significantly affect performance and work experience significantly affect performance. Work experience greater influence than the discipline of work, it is because employees who have more work experience, able to make a positive contribution to each employee who has no experience.